STYLISTIC FEATURES OF CHURCH MUSIC AFTER DIMITRIE CUNȚANU, A DEFAULT TYPOLOGY - MOCANU, Daniel (Studia Universitatis Babes-Bolyai Musica, 2023)
Present both in the melodies recorded by Dimitrie Cunțanu and in the melodies that we find in the oral tradition, modal constructions represent melodic molds for defining the central Transylvanian musical style. The correct framing of a melodic line is achieved by means of the scale, the cadential system and the melodic formulae. The ecclesiastical musical style according to Cunțanu, which was derived s from the Byzantine musical tradition, has become an individual style among ecclesiastical musical styles by uniquely assimilating various musical elements from folklore, music of the related cults, cultic music, and entertainment music. The resulting modal patterns have created a church style specific to the intra-Carpathian area, which has ossified into an autochthonous musical tradition. Indexing the modal constructions gives us an overview of the internal structures that underlie and individualize each mode.